Implementasi Program Sinau Bareng Sebagai Upaya Peningkatan Kualitas Pendidikan di Desa Bumiayu - Adi Wahyono; Anita Sari; Feri Raharjo; Filio Itsar Ma’ruf; Nurul Hidayah; M. Fendy Kusuma Hadi Sufyan (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
The Sinau Bareng work programme is an effective part of learning activities in an effort to improve the quality of the children of Bumiayu Village, Kajoran Sub-district, Magelang District. The purpose of this study to (1) obtain a description of learning planning, (2) learning implementation, and (3) learning evaluation to improve the quality of (2) learning implementation, and (3) learning evaluation to improve the quality of quality of education by applying the direct practice method of various subjects and activities. The research design was descriptive qualitative research. The research subjects were children from elementary to junior high school or equivalent in Desa Bumiayu village. The object of research is the planning, implementation, and evaluation of Sinau Bareng activities through hands-on methods. Sinau Bareng activities through direct practice methods. The data were collected through observation and documentation. The results of the study showed several things, (1)learning planning uses a variety of learning media, (2) the implementation of learning is proven to increase knowledge and enthusiasm for learning children of Bumiayu Village, and (3) evaluation of Sinau Bareng activities in the form of non-test evaluation.